Diagnostic power and clinical impact of exome sequencing in a cohort of 500 patients with rare diseases. Issue 4 (30th November 2020) - Quaio, Caio Robledo D'Angioli Costa; Moreira, Caroline Monaco; Novo‐Filho, Gil Monteiro; Sacramento‐Bobotis, Patricia Rossi; Groenner Penna, Michele; Perazzio, Sandro Felix; Dutra, Aurelio Pimenta; da Silva, Rafael Alves; Santos, Monize Nakamoto Provisor; de Arruda, Vanessa Yurie Nozaki; Freitas, Vanessa Galdeno; Pereira, Vinícius Ceola; et al.
Abstract: Rare diseases comprise a diverse group of conditions, most of which involve genetic causes. We describe the variable spectrum of findings and clinical impacts of exome sequencing (ES) in a cohort of 500 patients with rare diseases. In total, 164 primary findings were reported in 158 patients, representing an overall diagnostic yield of 31.6%. Most of the findings (61.6%) corresponded to autosomal dominant conditions, followed by autosomal recessive (25.6%) and X‐linked (12.8%) conditions. These patients harbored 195 variants, among which 43.6% are novel in the literature. The rate of molecular diagnosis was considerably higher for prenatal samples (67%; 4/6), younger children (44%; 24/55), consanguinity (50%; 3/6), gastrointestinal/liver disease (44%; 16/36) and syndromic/malformative conditions (41%; 72/175). For 15.6% of the cohort patients, we observed a direct potential for the redirection of care with targeted therapy, tumor screening, medication adjustment and monitoring for disease‐specific complications. Secondary findings were reported in 37 patients (7.4%). Based on cost‐effectiveness studies in the literature, we speculate that the reports of secondary findings may influence an increase of 123.2 years in the life expectancy for our cohort, or 0.246 years/cohort patient. ES is a powerful method to identify the molecular bases of monogenic disorders and redirect clinical care.